Hot fuzz [videorecording (Blu-Ray)] - Bevan, Tim; Park, Nira; Fellner, Eric; Wright, Edgar, 1974-; Wright, Edgar, 1974-; Pegg, Simon, 1970-; Pegg, Simon, 1970-; Frost, Nick, 1972-; Broadbent, Jim; Dalton, Timothy, 1944-; Woodward, Edward, 1930-2009; Whitelaw, Billie, 1932-2014; et al. (Universal Studios Home Entertainment, 2009)
Nicholas Angel is the finest cop London has to offer. He has an arrest record that is higher than any other officer on the force. As a result, Angel's superiors send him to a place where his talents won't be quite so obvious. They send him to the sleepy and seemingly crime-free village of Sandford. He is partnered with the well-meaning but overeager police officer Danny Butterman, who is the son of the police chief. Danny is a huge action movie fan and believes this may be his chance to experience the life of gunfights and car chases. However, as a series of grisly accidents rocks the village, Angel is convinced that Sandford is not what it seems and as the intrigue deepens, Danny's dreams of explosive, high-octane, car-chasing, gunfighting, all-out action seem more and more like a reality.